The Role Of Nursing Leadership Delegation And Pharmacies In Managing Workload And Staff Shortages During Crises (Journal of Namibian Studies : History Politics Culture, 2023)
In disasters, rapid implementation and maintenance of an effective mass prophylaxis or medical surge system require flexible use of all human resources in the institution. This might include medical or nursing students, volunteers, other college staff, or retirees who require initial assessment and training, ongoing supervision, and timely handling. Significant legal, accreditation, and institutional policy concerns about how best to place these individuals in a disaster operation that is under a condition, will not be licensed, not confused or qualified to practice without proper supervision or licensed professionals. Human resources experts, such as nursing professional leadership, can guide the principles, benefits, risks, legalities, guidelines for directing and delegating care during disasters that involve internally emerging portable dies panels, or that threaten to overwhelm healthcare. Congestion and overload can be multifaceted. Interview concerns all available resources to support the professionals who normally provide care for the individual's high quality. These concerns can also influence the worker's general well-being, which can be to the implementation of employee jeopardizes patient quality of care.